2017
DOI: 10.1021/acssuschemeng.7b02511
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Conductor Sr2Fe1.5Mo0.5O6−δ as Robust Fuel Electrode for Pure CO2 Reduction in Solid Oxide Electrolysis Cell

Abstract: Electrolysis of carbon dioxide to carbon monoxide, through which the greenhouse gas could be effectively utilized, using solid oxide electrolysis cells is now attracting much interest. Here, we show for the first time that the redox-stable Sr 2 Fe 1.5 Mo 0.5 O 6−δ (SFM) ceramic electronic-ionic conductor can be used as the electrocatalyst to electrolyze and convert 100% CO 2 to CO without using any safe gases like H 2 and CO. SFM maintained its cubic structure and had an electrical conductivity of 21.39 S cm −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 49 publications
(86 reference statements)
4
83
0
Order By: Relevance
“…Many mixed-conducting perovskite-type oxides have been tested for use as cathode for CO 2 electrolysis such as La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3 (LSCM), [6][7][8] La x Sr 1Àx TiO 3Àd (LST), [9][10][11] La 0.8 Sr 0.2 FeO 3Àd (LSF), 12 and Sr 2 Fe 1.5 Mo 0.5 O 6Àd (SFM). [13][14][15] Amongst these, the iron-based materials LSF and SFM are reported to exhibit the highest electrocatalytic activity for CO 2 reduction in the intermediate to high temperature range (600-850 C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many mixed-conducting perovskite-type oxides have been tested for use as cathode for CO 2 electrolysis such as La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3 (LSCM), [6][7][8] La x Sr 1Àx TiO 3Àd (LST), [9][10][11] La 0.8 Sr 0.2 FeO 3Àd (LSF), 12 and Sr 2 Fe 1.5 Mo 0.5 O 6Àd (SFM). [13][14][15] Amongst these, the iron-based materials LSF and SFM are reported to exhibit the highest electrocatalytic activity for CO 2 reduction in the intermediate to high temperature range (600-850 C).…”
Section: Introductionmentioning
confidence: 99%
“…Isomorphic substitution of A-or B-sites by other types of cations is a known strategy to optimize the performance of perovskite oxide electrodes. [16][17][18][19][20][21][22][23][24][25] In previous research, [13][14][15] we showed that the double perovskite SFM is a promising electrode material for pure CO 2 electrolysis. Aiming at further promoting the rate of CO 2 reduction at the SFM surface, we have investigated in this work the inuence of partial substitution of Fe in SFM by Mn (to produce Sr 2 Fe 1.4 Mn 0.1 Mo 0.5 O 6Àd (SFMM0.1)) on its effectiveness as a cathode material for CO 2 electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Even though, carbon deposition is still unavoidable in Ni-YSZ cathode. [17][18][19] Compared to the traditional SOEC, symmetrical cell configuration that consists of the same material composition for both anode and cathode is of great interest with advantages of better compatibility and low cost. [16] To avoid these issues, cathode without Nibased cermet electrode has been tried.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the major symmetrical electrodes of S-SOEC are from SOFC, such as Sr 2 Fe 1.5 Mo 0.5 O 6-δ , [18,23] La x Sr 1-x Co y Fe 1-y O 3-δ , [21,24] and La x Sr 1-x Fe y Ni 1-y O 3-δ. [25,26] Spinel oxides with considerable conductivity, suitable structural stability and high reaction activity, have been widely investigated as electrodes for many energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation